Detection of eicosanoids in epiretinal membranes of patients suffering from proliferative vitreoretinal diseases. Issue 1 (1st January 1997) - Augustin, Albert J; Grus, F H; Koch, F; Spitznas, M
Abstract : AIM: Arachidonic acid is metabolised via lipoxygenase to 15-HETE (15-hydroxyeicosatetraenoic acid) and 15-HPETE (15-hydroperoxyeicosatetraenoic acid), which are believed to influence proliferation in tissue culture. 15-HETE is the reduction product of 15-HPETE. Cell proliferation is believed to be decreased by 15-HPETE and increased by 15-HETE. The aim of this study was to investigate epiretinal membranes for the presence of these lipoxygenase products and to compare membranes from different disease processes. METHODS: Epiretinal membranes of 15 patients suffering from proliferative vitreoretinopathy (PVR, n=7) and proliferative diabetic retinopathy (PDR; n=8) were removed during vitrectomy and analysed by means of thin layer chromatography. The plates were evaluated by digital image analysis. RESULTS: Both 15-HETE and 15-HPETE were identified in membranes from eyes of patients with PVR and PDR with HETE values significantly higher (p<0.05) than HPETE values (HETE/HPETE ratio = 5.2). CONCLUSION: This study demonstrates that eicosanoids are present in the epiretinal membrane tissue of patients with PVR and PDR. Considering that HETE increases cell proliferation while HPETE inhibits it, it is conceivable that eicosanoids are an additional factor contributing to the regulation of membrane growth in proliferative retinal disorders. Thus, inhibition of lipoxygenase could be a therapeutic approach in these diseases.